Analysis, control and optimal operations in hybrid power systems : advanced techniques and applications for linear and nonlinear systems - Bizon, Nicu; Shayeghi, Hossein; Mahdavi Tabatabaei, Naser (London : Springer, 2013)
The book's text focuses on explaining and analyzing the dynamic performance of linear and nonlinear systems, in particular for Power Systems (PS) including Hybrid Power Sources (HPS). The system stability is important for both PS operation and planning. Placing emphasis on understanding the underlying stability principles, the book opens with an exploration of basic concepts using mathematical models and case studies from linear and nonlinear system, and continues with complex models and algorithms from field of PS.
-- Overview of hybrid power systems -- Revisiting and generalizing Barkhausen's equality -- State enerty-based approach as a tool for design and simulatin of linear and nonlinear systems -- Power systems stability analysis based on classical techniques in work -- Optimal design of UPFC based damping controller using PSO and QPSO -- Application of PSO and GA for transmission network expansion planning -- Applications in control of hybrid power systems.
Includes bibliographical references and index.
Keywords: Electric power systems; Engineering; Hybrid power systems; Renewable energy sources